2020
DOI: 10.31686/ijier.vol8.iss9.2659
|View full text |Cite
|
Sign up to set email alerts
|

Review of Clinical Factors That Cause Acne Vulgaris

Abstract: Acne vulgaris is a common skin disorder caused by inflammation and/or blockage of the pilosebaceous follicle. This research is a literature review study that is descriptive in nature and seeks to compile information on the factors related to the etiopathogenesis of the clinical manifestations of acne vulgaris. A survey was conducted in the Web of Science database in the period from January to May 2019, using the keywords "acne vulgaris, etiopathogenesis and pathophysiology". The etiopathogenesis of acne vulgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Being overweight, smoking, under distress, having irregular menstrual cycles, and eating too many nuts could be other factors showing a strong connection for acne [36]. Compared to such findings, research from Italy revealed a link between tobacco and acne [37].…”
Section: Resultsmentioning
confidence: 91%
“…Being overweight, smoking, under distress, having irregular menstrual cycles, and eating too many nuts could be other factors showing a strong connection for acne [36]. Compared to such findings, research from Italy revealed a link between tobacco and acne [37].…”
Section: Resultsmentioning
confidence: 91%
“…Over 650 million individuals, or 9.4% of the world's population, are impacted. While acne vulgaris is the most prevalent illness in adolescents, little has been published regarding its complex pathogenesis [1] . Acne vulgaris is caused by a variety of variables, including genetics, food, hormones, stress, and environment [2] .…”
Section: Introductionmentioning
confidence: 99%